(untitled) (Sciences & Technologie. C, Biotechnologies, 2007)
This work was a study of the growth of the larvae of Apis mellifera intermissa fed on different diets and reared by techniques designed for the purpose of following the growth of each individual larva and its transformation into nymph and adult. The experiments were carried out at 34°C and at a relative humidity of 100%. -Optimum larval growth was obtained with a mixture of 80% royal jelly in the honey. -Experiments with royal jelly defatted by acetone and ether, gave a fair percentage of successes which showed that decenoic acid did not play a determining role in larval development. Experiments carried out with royal jelly treated with warm benzene or with boiling alcohol gave no results, the jelly having deteriorated . -Freeze-drying of the royal jelly did not interfere with larval development. -The addition of proteins to the royal jelly did not improve, but seemed rather to slow down larval development.